THE ROLE OF MOTIVATION IN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Tugalov, Ismat; Hotamova, Jasmina (Scientific practical conference, 2025)
This paper explores the importance of motivation in learning a foreign language. Motivation can be categorized into intrinsic and extrinsic factors, both of which significantly influence learners’ engagement and progress. Intrinsic motivation is driven by personal interest and self-development, while extrinsic motivation is linked to external goals such as exams, jobs, or study opportunities. Teachers play a crucial role in sustaining motivation by applying interactive methods, recognizing students’ achievements, and using modern technologies. The study concludes that motivation is the cornerstone of effective foreign language learning, and educators should actively foster it to achieve better outcomes.